The effectiveness of using reciprocal technique in developing the skillful self and teaching some basic football skills among literary fifth grade students - MUSA ADNAN ALANI (physical education and sport sciences college for women/ Baghdad University, 2021)
ABSTRACT   The research aims to know the effectiveness of the use of reciprocal style in developing the skillful self and learning some basic skills in football among fifth grade literary students as well as knowing which is better (reciprocal style or the method used) in the variables of the current study, the researcher used the experimental approach to suit the nature of the research as for the research sample It was represented by the literary fifth grade students in Anah Preparatory School for Boys, and the number (20) students were divided into two groups by (10) students for each group, for whom pre-tests were taken on the scale of self-skill and basic skills in football.                  Then the experimental group applied its independent variable (the reciprocal method), then the control group applied (the method used), and the researcher applied the principle of the gradation from easy to difficult in implementing the exercises during the lesson session, and the results were processed by the statistical bag program (SPSS), and the researcher concluded that Positive effectiveness in developing self-skill and learning some basic football skills among literary fifth-grade students, and the researcher recommended using this method in other activities and paying attention to all soccer skills in football.